2015
DOI: 10.1186/s13018-015-0175-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of percutaneous nucleoplasty with coblation on phospholipase A2 activity in the intervertebral disks of an animal model of intervertebral disk degeneration: a randomized controlled trial

Abstract: BackgroundThis randomized controlled trial was carried out to (1) evaluate the effect of nucleoplasty with coblation on the PLA2 activity in the degenerative intervertebral disks of an animal model and (2) explore the possible therapeutic mechanism of coblation in addition to the current theory, which focuses on decreasing the intradiskal pressure in the treatment of intervertebral disk degeneration.MethodsThirty-six animal models of intervertebral disk degeneration were successfully established and then rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…PLA2 enzymes catalyze the hydrolysis of glycerophospholipids in the cellular membrane to produce free fatty acids, such as arachidonic acid (AA), which are used through the COX pathway to produce prostaglandins and other inflammatory mediators (Chacur et al, 2004; Svensson et al, 2005). sPLA2 increases in many painful conditions including discogenic pain (Ren et al, 2015), spinal cord injury (Titsworth et al, 2009), and inflammatory pain (Svensson et al, 2005) and its direct application to normal nerve tissue induces behavioral sensitivity (i.e. pain) and immune cell activation in the spinal cord (Chacur et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…PLA2 enzymes catalyze the hydrolysis of glycerophospholipids in the cellular membrane to produce free fatty acids, such as arachidonic acid (AA), which are used through the COX pathway to produce prostaglandins and other inflammatory mediators (Chacur et al, 2004; Svensson et al, 2005). sPLA2 increases in many painful conditions including discogenic pain (Ren et al, 2015), spinal cord injury (Titsworth et al, 2009), and inflammatory pain (Svensson et al, 2005) and its direct application to normal nerve tissue induces behavioral sensitivity (i.e. pain) and immune cell activation in the spinal cord (Chacur et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…PPDD shows its effect by down-regulating local inflammatory mediators, reducing disc size, and initiating the repair process. Ren et al [ 19 ] found that PPDD effectively degraded phospholipase A2 (PLA2) activity. PLA2 activity is closely associated with intervertebral disc degeneration, intervertebral disc herniation, radicular pain, and lumbar discogenic pain.…”
Section: Discussionmentioning
confidence: 99%
“…In two long-term follow-up studies conducted in China, PPDD was shown to be effective for pain relief and function improvement for 2–3 years. However, there is no significant difference between the 3- and 5-year postoperative VAS and ODI scores, and excellent or good patient satisfaction was 87.9% at 1 week, 72.4% at 1 year, 67.7% at 3 years, and 63.4% at 5 years [ 19 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These hydrolysis products are well-known mediators of inflammation and tissue damage; , specifically, the hydrolyzed free fatty acids are used in the cyclooxygenase pathways to produce prostaglandins and other inflammatory molecules . Additionally, increased sPLA 2 expression has been reported in many different persistent pain states that are characterized by inflammation, including intervertebral disc degeneration and spinal cord injury . After a peripheral neuropathic injury such as constriction of the sciatic nerve, sPLA 2 expression increases in both the DRG and the spinal cord .…”
Section: Therapeutic Targets and Materials For Painmentioning
confidence: 99%